Virtual Environment for an Ants-like Model - Hamada, Mohamed (International Journal of Virtual Reality, 2010)
In this paper we introduce an integrated virtual environment of ants-like agents based on ants’ behavior. Our system can simulate the behavior of ants-like agents under various conditions and environment changes. In our model the ants are moving in random on an environment that contains a randomly distributed source of food. Ants move with some simple rules and can change direction according to environmental information. We test this model with various situations and conditions of the environment to study how the system works with the pheromone information. In the aim of realizing the practical implication of our model, a web-based computer simulation is given. This simulation enables the study and test for the model under different circumstances of the environmental conditions